Virtual Teams: Taking Stock and Moving Forward - Handke, Lisa; Costa, Patrícia; O’Neill, Thomas A. (Small Group Research, 2024)
The papers in this Special Issue show that virtual teamwork is a complex phenomenon that depends on a multiplicity of team, task, and environmental factors. In this editorial, we begin with a short review of the main perspectives through which virtual teams have been studied. From there, we move to an overview of the papers in this Special Issue. To conclude, we discuss potential avenues for future research based on the collection of papers in this issue.
CRIS-Team Scopus Importer:2024-09-06
Keywords: computer-mediated communication; teamwork; virtual groups